A study on financial literacy level among generation Y in Melaka / Farahin Ab Rahman and Nurul Syafiqkah Nordin - Ab Rahman, Farahin; Nordin, Nurul Syafiqkah (Faculty of Business and Management, 2015)
Nowadays, the number of Generation Y that has financial problem and bankruptcy are keeping increasing. Accordingly, the purposed of this study is to study the Level of Financial Literacy among Generation Y in Malacca City. A field study was conducted in Malacca City, where 150 questionnaires were distributed at AEON Bandaraya Melaka, TESCO, and Jalan Hang Tuah but only 130 questionnaires were collected back. The data will interpret using Descriptive Analysis, Pearson Coefficient Correlation (r), and Regression Analysis. In order, to explain the level of Financial Literacy, Motivation, knowledge and Culture among Generation Y the researchers are using Descriptive Analysis. Overall, the respondent has high level of Financial Literacy and Motivation following by Knowledge and Culture on the average level in this study. Based on this study, it is good to increase the level of Motivation of Generation Y in order to make them have high level of Financial Literacy.